High‐Rate Alkaline Water Electrolysis at Industrially Relevant Conditions Enabled by Superaerophobic Electrode Assembly - Lingjiao Li; Petrus C. M. Laan; Xiaoyu Yan; Xiaojuan Cao; Martijn J. Mekkering; Kai Zhao; Le Ke; Xiaoyi Jiang; Xiaoyu Wu; Lijun Li; Longjian Xue; Zhiping Wang; et al. (Advanced Science, 2023)
Abstract Alkaline water electrolysis (AWE) is among the most developed technologies for green hydrogen generation. Despite the tremendous achievements in boosting the catalytic activity of the electrode, the operating current density of modern water electrolyzers is yet much lower than the emerging approaches such as the proton‐exchange membrane water electrolysis (PEMWE). One of the dominant hindering factors is the high overpotentials induced by the gas bubbles. Herein, the bubble dynamics via creating the superaerophobic electrode assembly is optimized. The patterned Co‐Ni phosphide/spinel oxide heterostructure shows complete wetting of water droplet with fast spreading time (≈300 ms) whereas complete underwater bubble repelling with 180° contact angle is achieved. Besides, the current collector/electrode interface is also modified by coating with aerophobic hydroxide on Ti current collector. Thus, in the zero‐gap water electrolyzer test, a current density of 3.5 A cm−2 is obtained at 2.25 V and 85 °C in 6 m KOH, which is comparable with the state‐of‐the‐art PEMWE using Pt‐group metal catalyst. No major performance degradation or materials deterioration is observed after 330 h test. This approach reveals the importance of bubble management in modern AWE, offering a promising solution toward high‐rate water electrolysis.